High acceptability of newborn screening for sickle cell disease among post-natal mothers in Western Kenya - John Orimbo; Shehu Shagari Awandu; Faith Muhonja; Patrick Owili; Dickens Omondi (PLoS ONE, 2025)
Sickle cell disease is a genetically inherited blood disorder that manifests early in life with resultant significant health complications. Globally, nearly three quarters of all affected babies are in sub-Saharan Africa. Early identification of babies with sickle cell disease through newborn screening followed by early linkage to care is recommended. However, the program has not been widely adopted in the sub-Saharan Africa. The Kenyan ministry of health, in 2020, published a policy on newborn screening for sickle cell disease from levels 2–6 healthcare facilities. However, evidence on acceptability of newborn screening to scale up newborn screening program is scarce. Few studies have been conducted across the sub-Saharan Africa to assess the acceptability of newborn screening for sickle cell disease with conflicting results. This study assessed factors associated with acceptability of newborn screening among mothers of newborns delivered at Homa bay county teaching and referral hospital, western Kenya. This study employed a cross-sectional design among postnatal mothers at Homa bay county teaching and referral hospital with 399 postnatal mothers enrolled into the study. After obtaining informed consent from the postnatal mothers, a semi-structured questionnaire was used for data collection. Maternal sociodemographic characteristics, knowledge, and perception were assessed. Babies were also screened for sickle cell disease using Sickle SCAN point-of-care test. The acceptability was calculated as percentage of mothers accepting to have their babies screened. Data were analyzed using logistic regression to explore factors associated with acceptability of newborn screening for sickle cell disease. Ninety-four percent of mothers accepted newborn screening for sickle cell disease. Only maternal age and occupation were significantly associated with acceptability of newborn screening for sickle cell disease. Mothers aged 25−34 years were 3 times less likely to accept newborn screening for sickle cell disease than those younger mothers than 25 years (OR=0.33;95%CI = 0.13–0.86; p = 0.024).Similarly, mothers in the formal employment were 6 times less likely to accept newborn screening for sickle cell disease than those who were students (OR= 0.16; 95%CI = 0.03–0.84; p = 0.031).Mothers who were in formal employment were 25 times less likely to accept newborn screening for sickle cell disease than those who were students in the multivariate logistic analysis model (aOR= 0.04; 95% CI = 0.00–0.78 ; p = 0.034). The acceptability of newborn screening for sickle cell disease is high in the county. The Homabay county ministry of health should implement routine newborn screening for sickle cell disease in all healthcare facilities conducting deliveries of newborns.